2014
DOI: 10.1039/c4cp00403e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the O(3P) + CH4 hydrogen abstraction reaction at hyperthermal collision energies

Abstract: Motivated by recent experiments on the title reaction at the high collision energy of 64 kcal mol(-1) reported by Minton et al., a detailed dynamics study was carried out using quasi-classical trajectory (QCT) calculations based on an analytical potential energy surface recently developed by our group, PES-2014. Our results reproduce the experimental evidence: most of the available energy appears as translational energy (80 ± 10%) and scattering distribution is forward, suggesting a stripping mechanism associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…With regard to the vibrational ground-state reaction, O( 3 P) + CH 4 (ν = 0), the experimental studies [1][2][3][4][5] have shown that this reaction leads to cold rotational and non-inverted vibrational distributions of the OH product, low vibrational excitation of the CH 3 co-product, and a backward scattering angular distribution. The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 86%
“…The theoretical studies [6][7][8][9][10][11][12][13][14] are consistent with the experimental finding, associated with a rebound mechanism with a narrow cone of acceptance and a collinear CH 3 -H -O transition state. Recently, we reported a series of theoretical QCT studies [12][13][14] based on a new potential energy surface (PES-2014) developed by our group, 12 which is a full-dimensional analytical surface fitted exclusively to high-level ab initio calculations. These dynamics studies were performed at low, 8-20 kcal mol −1 , and high, 64 kcal mol −1 , collision energies, and reproduce the experimental data.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…These PESs have recently been used for quasi-classical trajectory (QCT) and reduced-dimensional quantum dynamics computations. [7][8][9][10] In 2014 an experimental study also appeared investigating the effects of the antisymmetric stretching excitation on the angular distributions of the O( 3 P) + CH 4 (v 3 = 0, 1) reactions. 11 The experiment found that the angular distributions are backward scattered for the groundstate reaction and shift toward sideways and forward directions upon stretching excitation.…”
mentioning
confidence: 99%
“…30,54,55 Again, the ground-state reaction has been extensively investigated and is characterized by a direct abstraction pathway with the rebound mechanism. 35,36,[56][57][58][59][60][61][62][63] This is to be contrasted to the ground-state reaction of F + CHD 3 , for which dual mechanisms partake: a direct abstraction and a resonance-mediated pathway that prevails at lower collision energies. 38,39 Figure 3 illustrates the effects of CH stretch-excitation of CHD 3 (v 1 = 1) on the CD 3 (v = 0) product, which is the dominant product channel.…”
Section: O( 3 P) + Chd 3 (V 1 = 1): a Central Barrier Reactionmentioning
confidence: 99%